SISTEM MONITORING ENERGI LISTRIK PADA KWH-METER PRABAYAR BERBASIS INTERNET OF THINGS (IoT) - Nur Aminah; Rusdi Wartapane; Reski Praminasari (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research aims to design a digital KWHmeter with a prepaid system. The digital KWHmeter is designed using ESP32 as a microcontroller module that supports Wifi network connectivity to build an Internet of Things (IoT) system. The platform is formed between digital KWHmeter and Smartphone/gadget. As a result, electricity conditions in residential homes can be monitored remotely by utilizing the internet network. With this monitoring system, consumers can turn on/off the household electrical system remotely. Monitoring the gadget layout shows the amount of current, voltage, power and power factor. Apart from that, the gadget layout can also input the KVA/electricity credit value as a simulation of electricity tokens. The remaining electricity credit will be sent to the Telegram application as a notification